(untitled) (Journal of Patan Academy of Health Sciences, 2015)
Nursing perspective is different from doctors. It is a known fact that doctors and nurses must work together for the better patient care. It is very important for doctors to know how nursing services are provided. Moreover a good communication and team work is an essence of present medical service. So, this attitude should be embedded in the medical education to decrease professional distance and increase mutual respect in future. PAHS has provided this opportunity as a nursing posting with a vision of holistic teaching of medical students and shaping a positive attitude towards all health care providers. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13022 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):61-63